Activity of the Novel Peptide Arminin against Multiresistant Human Pathogens Shows the Considerable Potential of Phylogenetically Ancient Organisms as Drug Sources - Augustin, René (American Society for Microbiology (ASM), 2009)
The emergence of multidrug-resistant bacteria highlights the need for new antibacterial agents. Arminin 1a is a novel antimicrobial peptide discovered during investigations of the epithelial defense of the ancient metazoan Hydra. Following proteolytic processing, the 31-amino-acid-long positively charged C-terminal part of arminin 1a exhibits potent and broad-spectrum activity against bacteria, including multiresistant human pathogenic strains, such as methicillin-resistant Staphylococcus aureus (MRSA) strains (minimal bactericidal concentration, 0.4 μM to 0.8 μM). Ultrastructural observations indicate that bacteria are killed by disruption of the bacterial cell wall. Remarkably, the antibacterial activity of arminin 1a is not affected under the physiological salt conditions of human blood. In addition, arminin 1a is a selective antibacterial agent that does not affect human erythrocyte membranes. Arminin 1a shows no sequence homology to any known antimicrobial peptide. Because of its high level of activity against multiresistant bacterial strains pathogenic for humans, the peptide arminin 1a is a promising template for a new class of antibiotics. Our data suggest that ancient metazoan organisms such as Hydra hold promise for the detection of novel antimicrobial molecules and the treatment of infections caused by multiresistant bacteria.